In Vitro Antilisterial Properties of Crude Methanol Extracts of Garcinia kola (Heckel) Seeds - Dambudzo Penduka; Anthony I. Okoh (The Scientific World Journal)
Crude methanol extracts of Garcinia kola (Heckel) seeds were screened for their antilisterial activities against 42 Listeria bacteria isolated from wastewater effluents. The extract had activity against 45% of the test bacteria and achieved minimum inhibitory concentrations (MICs) ranging between 0.157 and 0.625 mg/mL. The rate of kill of the extract was determined against four representative Listeria species in the study, and the results showed that the highest percentage of bacteria cells were killed after the maximum exposure time of 2 h at the highest concentration of 4×MIC value, with the maximum number of bacteria cells killed being for L. ivanovii (LEL 30) 100%, L. monocytogenes (LAL 8) 94.686%, L. ivanovii (LEL 18) 60.330%, and L. grayi (LAL 15) 56.071% We therefore conclude that the nature of inhibition of the crude methanol extracts of Garcinia kola seeds can be either bactericidal or bacteriostatic depending on the target Listeria species and can also differ among same species as evidenced by L. ivanovii strains LEL 30 and LEL 18.